Antibiotic Resistance in Clinical Medicine - Shah, Santosh; Kasarla, Rajeshwar Reddy; Yadav, Nikita Singh; Shrestha, Anjita; Gautam, Sadhana; Chaudhary, Sushil Kumar (Journal of Universal College of Medical Sciences, 2022)
Since the discovery of penicillin, antibiotics have been a cornerstone in modern medicine and signiﬁcantly improved global health. And while decades of overuse, misuse and abuse of antibiotics in hospitals, and in general population, at an ever increasing rate, both when they are needed and when they are not, in human beings and animals have accelerated the emergence and spread of resistant bacteria. Indiscriminate use of antibiotics in veterinary practice, and in animal feeds led to emergence of drug resistant strains, that are transferred to humans. This emergence of drug resistance is a major problem worldwide in antibiotic therapy. Infections caused by resistant microorganisms often fail to respond to the standard treatment, resulting in prolonged illness, longer hospital stays, higher healthcare expenditures, and greater risk of death. This article reviews and focuses on various aspects of development and mechanisms of antibiotic resistance in bacteria, and preventive measures to ﬁght the emerg- ing antibiotic resistance threat.